Процессы и механизмы взаимодействия лазерного излучения с твердыми средами (Обзор) - Манжелеевский, С.В.; Санин, А.Ф. (Вісник Українського матеріалознавчого товариства, 2013)
Processes that occur in the interaction of laser radiation with a solid medium, established the basic dependence of the temperature distribution are investigated. The analysis of the mechanism of degradation of materials as a result of exposure to laser radiation.